2020
DOI: 10.7717/peerj.9399
|View full text |Cite
|
Sign up to set email alerts
|

Elephants in the neighborhood: patterns of crop-raiding by Asian elephants within a fragmented landscape of Eastern India

Abstract: Loss of forest cover, rise in human populations and fragmentation of habitats leads to decline in biodiversity and extinction of large mammals globally. Elephants, being the largest of terrestrial mammals, symbolize global conservation programs and co-occur with humans within multiple-use landscapes of Asia and Africa. Within such shared landscapes, poaching, habitat loss and extent of human–elephant conflicts (HEC) affect survival and conservation of elephants. HEC are severe in South Asia with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 65 publications
4
11
0
Order By: Relevance
“…In the study area, elephants are the most predominant cause for crop loss due to wildlife in the region. This finding is supported by the previous studies in the region which looked at the distribution of elephants as well as crop losses due to elephants (Roy et al, 2017;Kshettry et al, 2020;Naha et al, 2020). However, this study for the first time compared losses due to wildlife with all reasons for crop damage in the region.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the study area, elephants are the most predominant cause for crop loss due to wildlife in the region. This finding is supported by the previous studies in the region which looked at the distribution of elephants as well as crop losses due to elephants (Roy et al, 2017;Kshettry et al, 2020;Naha et al, 2020). However, this study for the first time compared losses due to wildlife with all reasons for crop damage in the region.…”
Section: Discussionsupporting
confidence: 84%
“…Proximity to forests had an effect on the crop damage with villages within 1.5 km of forests reporting wildlife as the main cause for damage whereas villages further away reported insect pests as the main source of crop damage (Figure 3). A previous study conducted in the landscape has also found crop damage due to elephants was high within a 1.5 km buffer of forested areas (Naha et al, 2020). We also found that the wildlife species apart from elephants were also responsible for crop damage, albeit at low proportions including species, such as peafowl, wild pig, and macaque.…”
Section: Discussionsupporting
confidence: 71%
“…Mixed herd elephants rarely attacked humans (<5% of the incidents) although they are involved in crop raiding during migration through agriculture areas or settlements (Naha et al., 2020 ). Solitary adult bull elephants caused majority of attacks on humans in Nepal (Acharya et al., 2016 ) but it varied among elephant individuals.…”
Section: Discussionmentioning
confidence: 99%
“…According to Tripathy et al [26], since house damage occurred frequently in the villages of the study area, we assumed that elephant detection might be higher near rural built-up, especially in the forest fringe zone, while there will be lesser detection closer to urban areas. Although elephants prefer to forage in croplands, which are an easily accessible food source, crop raiding is a source of HEC [53,[92][93][94], which poses a serious threat to elephants. We used a Sentinel-2 Level-1C product of 10 m resolution to extract settlements, croplands, water bodies, and mining, which was later improved for classification accuracy using Google Earth products.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Elephants struggle to live in human-populated areas, due to the negative impacts of linear infrastructure (road and railway networks, drains, canals, and wells), mining, settlements, and electrocution, along with retaliatory killing [92,[94][95][96][97]. Elephants were present even in areas with a human density of ~2300 persons/km 2 in the central region of the study area; whereas, a previous study [103] had stated that elephants did not coexist with humans when the density reached ~15.6 persons/km 2 .…”
Section: Variables Influencing Elephant Detectionmentioning
confidence: 99%